Anti- versus Pro-Competitive Mergers - Sven-Olof Fridolfsson (Research Institute of Industrial Economics (IFN), 2007)
In a framework where mergers are mutually excluding, I show that firms pursue anti- rather than (alternative) pro-competitive mergers. Potential outsiders to anti-competitive mergers refrain from pursuing pro-competitive mergers if the positive externalities from anti-competitive mergers are strong enough. Potential outsiders to pro-competitive mergers pursue anti-competitive mergers if the negative externalities from the pro-competitive mergers are strong enough. Potential participants in anti-competitive mergers are cheap targets due to the risk of becoming outsiders to pro-competitive mergers. Firms may even pursue an unprofitable and anti-competitive merger, when alternative mergers are profitable and pro-competitive.
Keywords: L12; L13; L41; 330; Anti- and Pro-Competitive Mergers; Consumers' Welfare; Coalition Formation; Endogenous Split of Surplus; Fusion; Wettbewerbsbeschränkung; Konsumentenrente; Wirtschaftsmodell